2016
DOI: 10.1155/2016/5719470
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Retrospective Survey regarding Diabetic Ketoacidosis Management in Italian Children with Type 1 Diabetes

Abstract: We conducted a retrospective survey in pediatric centers belonging to the Italian Society for Pediatric Diabetology and Endocrinology. The following data were collected for all new-onset diabetes patients aged 0–18 years: DKA (pH < 7.30), severe DKA (pH < 7.1), DKA in preschool children, DKA treatment according to ISPAD protocol, type of rehydrating solution used, bicarbonates use, and amount of insulin infused. Records (n = 2453) of children with newly diagnosed diabetes were collected from 68/77 centers (87%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 21 publications
6
30
0
Order By: Relevance
“…In mainland Italy, DKA frequency at time of diabetes diagnosis (41.9%) was consistent with recent reports from other countries, such as France (43.9%)14 and Brazil (42.3%)15, and with a recent Italian study based on two years of observation (38.5%)7. The DKA frequency in Italian children at diagnosis of type 1 diabetes was somewhat higher than that reported in Austria (34.0%)5, Germany (21.1%)3, New Zealand (25.0%)16 and the U.S. (31.1%)17 and, disappointingly, close to twice that reported in Finland (22.4%)18 and Denmark (17.9%)19 and in Canada (18.6%)20.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In mainland Italy, DKA frequency at time of diabetes diagnosis (41.9%) was consistent with recent reports from other countries, such as France (43.9%)14 and Brazil (42.3%)15, and with a recent Italian study based on two years of observation (38.5%)7. The DKA frequency in Italian children at diagnosis of type 1 diabetes was somewhat higher than that reported in Austria (34.0%)5, Germany (21.1%)3, New Zealand (25.0%)16 and the U.S. (31.1%)17 and, disappointingly, close to twice that reported in Finland (22.4%)18 and Denmark (17.9%)19 and in Canada (18.6%)20.…”
Section: Discussionsupporting
confidence: 90%
“…Although the frequency of DKA varies widely between countries, levels of DKA at diagnosis of type 1 diabetes seem to be constant in Germany3, Great Britain4, Austria5 and the Unites States6. A recent Italian study on DKA incidence at diagnosis in Italy during the calendar years 2012–2013 showed a higher frequency of DKA in subjects under 18 years of age than that observed in Northern European countries7. The Parma campaign demonstrated the effectiveness of a public education programme in reducing the frequency of DKA at diabetes diagnosis in a restricted area.…”
mentioning
confidence: 99%
“…There is wide geographic variation in the frequency of DKA at onset of diabetes; rates inversely correlate with the regional incidence of type 1 diabetes. Frequencies range from approximately 15% to 70% in Europe and North America . DKA at diagnosis is more common in younger children (especially <2 years of age), including infants with both transient and permanent neonatal diabetes (overall frequency 66%), often the consequence of diagnostic error or delayed treatment .…”
Section: Frequency Of Dkamentioning
confidence: 99%
“…Skitch and Valani[23] looked at the protocols of thirteen pediatric tertiary centers in Canada and reported many differences in the management of DKA. In comparison, a survey in pediatric centers in the Italian Society for Pediatric Diabetology and Endocrinology recognized significant differences in DKA management among their centers as well[24]. Both articles reference the need for evidence-based guidelines to be utilized across the board for best practice[23,24].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, a survey in pediatric centers in the Italian Society for Pediatric Diabetology and Endocrinology recognized significant differences in DKA management among their centers as well[24]. Both articles reference the need for evidence-based guidelines to be utilized across the board for best practice[23,24]. Although, DKA is managed through different methods, preventative care for these patients is of utmost importance.…”
Section: Discussionmentioning
confidence: 99%